1978
DOI: 10.1093/oxfordjournals.jbchem.a132234
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-Coenzyme A Synthetase and Fatty Acid Oxidation in Rat Liver Peroxisomes

Abstract: Rat liver peroxisomes oxidized palmitate in the presence of ATP, CoA and NAD+, and the rate of palmitate oxidation exceeded that of palmitoyl-CoA oxidation. Acyl-CoA synthetase [acid: CoA ligase (AMP-forming); EC 6.2.1.3] was found in peroxisomes. The substrate specificity of the peroxisomal synthetase towards fatty acids with various carbon chain lengths was similar to that of the microsomal enzyme. The peroxisomal synthetase activity toward palmitate (40--100 nmol/min per mg protein) was higher than the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…The cross-contamination between fractions, calculated from the marker enzymes, was low except for the presence of marker enzymes for the mitochondrial outer membrane, peroxisomes and Percentage values microsomes in the particle-free supernatant. The distribution of amine oxidase and longchain acyl-CoA synthetase, an enzyme probably also localized to the peroxisomes [25], might indicate some fragmentation of the outer mitochondrial membrane and the peroxisomes. The high catalase activity found in the particlefree supernatant might, however, be due to 'soluble' catalase which is higher in male rats [26].…”
Section: Resultsmentioning
confidence: 99%
“…The cross-contamination between fractions, calculated from the marker enzymes, was low except for the presence of marker enzymes for the mitochondrial outer membrane, peroxisomes and Percentage values microsomes in the particle-free supernatant. The distribution of amine oxidase and longchain acyl-CoA synthetase, an enzyme probably also localized to the peroxisomes [25], might indicate some fragmentation of the outer mitochondrial membrane and the peroxisomes. The high catalase activity found in the particlefree supernatant might, however, be due to 'soluble' catalase which is higher in male rats [26].…”
Section: Resultsmentioning
confidence: 99%
“…The membranes were incubated with the primary antibody followed by alkaline phosphatase-conjugated goat anti-rabbit IgG. Immunoblotting was performed using rabbit polyclonal antibodies against rat acyl-CoA oxidase (AOX) (20), short chainspecific 3-ketoacyl-CoA thiolase (T1) (21), acetoacetyl-CoA thiolase (T2) (22,23), cytosolic thioesterase (CTE II) (24), short chain acyl-CoA dehydrogenase (SCAD) (25), medium chain acyl-CoA dehydrogenase (MCAD) (25), long chain acyl-CoA dehydrogenase (LCAD) (25), very long chain acyl-CoA dehydrogenase (VLCAD) (26), long chain acyl-CoA synthetase (LACS) (27), very long chain acyl-CoA synthetase (VLACS) (28), peroxisomal thiolase (PT) (21), carnitine palmitoyl-CoA transferase (CPT II) (29), short chain 3-hydroxyacyl-CoA dehydrogenase (SCHAD) (30), peroxisomal bifunctional protein (PH) (30), mitochondrial short chain specific hydratase (MH) (31), mitochondrial trifunctional protein ␣ and ␤ subunit (TP␣ and TP␤) (32), mitochondrial thioesterase I (MTEI) (33), and peroxisomal D-type bifunctional protein (DBF) (34).…”
Section: Materials-sodiummentioning
confidence: 99%
“…Four of the six (VLCAD, LCAD, LACS, and DBF) have highest catalytic activities with long chain fatty acid substrates (25)(26)(27)34), whereas the other two (SCHAD and T1) are more active with short and medium chain fatty acids (21,30). To evaluate the significance of the altered fatty acid ␤-oxidation enzymes, total hepatic ␤-oxidation was measured using lauric acid (C-12), palmitic acid (C-16), and lignoceric acid (C-24).…”
Section: Analysis Of Fattymentioning
confidence: 99%
“…Recently, a significant reduction in serum triglyceride levels and hepatomegaly was observed in rats following the administration of DEHP (16,34). It was also reported that DEHP caused an increase in catalase, fatty acyl-CoA oxidizing activity of homogenized rat livers, accompanied by a marked increase in peroxisomes and some ultrastructural changes of other cell organelles in rat liver cells, as were observed by the administration of common hypolipidemic agents, such as clofibrate and nafenopin (26,27,36).…”
mentioning
confidence: 93%